Acts of violence in the school setting: national and international responses - McCabe, Kimberly A. (Theory and practice in criminal justice series, 2020)
"Acts of School Violence in A School Setting provides accurate and practical information on school violence at a national and international level to students studying crime and criminal justice. In addition, this book provides information on victimization as it is perpetrated through the internet and focused upon students"--